2013
DOI: 10.5897/ajar2013.6742
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of crude tea extracts

Abstract: The tea polyphenols have been shown to possess many medicinal properties including antifungal activity, but there have been few studies regarding antifungal activity. The antifungal activity of tea polyphenols was evaluated on Candida albicans ATCC 90028 and a clinical isolate of Cryptococcus neoformans employing the disc diffusion assay. The minimum inhibitory concentration (MIC) of the tea polyphenols against C. albicans ATCC 90028 and a clinical isolate of C. neoformans was determined. Tea polyphenols showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…They are powerful antioxidants that provide several benefits [23]. Gallic acid and caffeine are also found in both aerated and non-aerated CTC and orthodox teas [15,19]. Figure 1 shows biomolecules of interest in this study found in tea.…”
Section: Introductionmentioning
confidence: 94%
“…They are powerful antioxidants that provide several benefits [23]. Gallic acid and caffeine are also found in both aerated and non-aerated CTC and orthodox teas [15,19]. Figure 1 shows biomolecules of interest in this study found in tea.…”
Section: Introductionmentioning
confidence: 94%
“…Tea is rich in polyphenols associated with numerous pharmacological properties such as; antimicrobial [5], anti-inflammatory [6], anti-aging [7, 8] antimalarial [9] and antioxidant activity [1, 3, 10]. Cancer, accelerated aging and other chronic disease associated with free radical induced oxidative damage [4] can be ameliorated by phytochemicals in tea since antioxidants in tea have been shown to protect DNA from damage induced by free radicals and slow or halt initiation and progression of cancerous tumor growth [12].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of tea against some bacteria and fungi has been demonstrated by several researchers (Arakawa, Maeda, Okubo, & Shimamura, 2004;Goto et al, 1998;Hamilton-Miller & Shah, 1999;Hamilton-Miller, 1997Ikigai, Nakae, Hara, & Shimamura, 1993;Koech & Wachira, 2013;Navarro-Martínez et al, 2005;Stapleton, Shah, Anderson, et al, 2004;Zhang & Rock, 2004). Depending on the type of processing, different tea have different active compounds responsible for these microbial activities.…”
Section: Antimicrobial Activity Of Tea Extractsmentioning
confidence: 99%
“…In order to address this issue and turn around the tea industry product diversification and value addition is required as is done in developed countries (Ochanda, 2010;Lelgo, Kamunya, Ochanda, & Wanyoko, 2011;Trienekens, 2011). Tea is usually used to fortify various foods due to its low pH (4.2) (Yilmaz, 2006), high polyphenol, antioxidant and potent antimicrobial activity (Almajano, Carbó, Jiménez, & Gordon, 2008;Jaziri, Slama, Mhadhbi, Gannoun, & Othman, 2005;Koech et al, 2013;Oh, Jo, Cho, Kim, & Han, 2013). This research focused on value addition of tea through the development of tea fortified yoghurts.…”
Section: Introductionmentioning
confidence: 99%